2015
DOI: 10.2174/1386207318666150525094503
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Breast Cancer Resistant Protein (BCRP) Inhibitors and Non-Inhibitors Using Machine Learning Approaches

Abstract: The breast cancer resistant protein (BCRP) is an important transporter and its inhibitors play an important role in cancer treatment by improving the oral bioavailability as well as blood brain barrier (BBB) permeability of anticancer drugs. In this work, a computational model was developed to predict the compounds as BCRP inhibitors or non-inhibitors. Various machine learning approaches like, support vector machine (SVM), k-nearest neighbor (k-NN) and artificial neural network (ANN) were used to develop the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…For example, Schyman et al ( 2017 ) used the variable nearest neighbor (vNN) method to develop 15 ADMET prediction models and to use them to quickly assess some potential drug candidates, including toxicity, microsomal stability, mutagenicity, and likelihood of causing drug-induced liver injury. Belekar et al ( 2015 ) developed a computational model to identify compounds as breast cancer resistance protein (BCRP) inhibitors or not by using various machine learning approaches like SVM, k-NN, and the artificial neural network (ANN). The prediction accuracy of all three approaches was over 85%.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…For example, Schyman et al ( 2017 ) used the variable nearest neighbor (vNN) method to develop 15 ADMET prediction models and to use them to quickly assess some potential drug candidates, including toxicity, microsomal stability, mutagenicity, and likelihood of causing drug-induced liver injury. Belekar et al ( 2015 ) developed a computational model to identify compounds as breast cancer resistance protein (BCRP) inhibitors or not by using various machine learning approaches like SVM, k-NN, and the artificial neural network (ANN). The prediction accuracy of all three approaches was over 85%.…”
Section: In Silico Approachesmentioning
confidence: 99%
“…This algorithm is model agnostic and not relevant to the specific structure of a model. A couple of previous studies only identified and analyzed the important features given by feature selection procedure for QSAR models [21,29,106] but did not explore the relationships between features and different QSAR models. It is quite possible that a set of important descriptors/fingerprints for a well-performing QSAR model may be not important to another QSAR model.…”
Section: Interpretation Of Qsar Modelsmentioning
confidence: 99%
“…However, we found that some descriptors/fingerprints related to molecular lipophilicity (BCUT_ SLOGP_2, GCUT_SLOGP_0, and SlogP_VSA5), molecular surface area, volume and shape (std_dim2, glob, and vsurf_descriptors) and electronic properties (PEOE_VSA_ descriptors and Q_VSA_POS) were captured by most well-performing models. The importance of molecular lipophilicity descriptors in the development of QSAR models to distinguish BCRP inhibitors from non-inhibitors has been highlighted by the previous studies [8,15,21]. Moreover, according to the two-step mechanism for the inhibition of Fig.…”
Section: Comparison With Published Models and Interpretation Of Modelsmentioning
confidence: 99%
See 2 more Smart Citations